Gingival phenotypes and their relation to age, gender and other risk factors - Wadhah Abdulnasser Alhajj (BMC, 2020)
Abstract Background Careful consideration and assessment of the type of phenotype has gained a fundamental importance in the treatment planning for any patient. We evaluated the prevalence of gingival phenotypes in a sample of Yemeni population and to explore its relationships to gender, age and other risk factors. Methods This cross-sectional study was performed among 456 patients. All maxillary anterior teeth were included for all parameters and 1st molars were included for gingival thickness measurements. All patients included in this study were systemically healthy and presented no dental crowding. Four clinical parameters were systematically recorded: Gingival thickness (GT), Width of keratinized gingiva (WKG), Crown width/ crown length (CW/CL) ratio and Papilla height (PH). Scores obtained from different parameters measurements were recorded and analyzed using non-parametric tests where P-value < 0.05 was considered significant. One examiner performed all measurements. Results The mean age was 29.9 ± 8.26 years. Of 456 recruited subjects, 83 (18.2%) subjects had thin, 69 (15.1%) had thick GT and 304 (66.7%) were placed in non-categorized (1.5-2 mm) GT. Square crown shape was found in 210 (44.1%) patients and 245 patients (55.9%) showed rectangular shape. Regarding WKG, 114 (25%) patients had width < 4 mm, 319 (70%) had width 4.1-8 mm and 23 (5%) patients had width >  8 mm. There was no significant difference between males and females for GT measurements. Regarding WKG, results showed that the prevalence of WKG 4.1-8 mm was more among females while males had more prevalence of ≤4 mm with significance difference. PH showed no significant differences between males and females. Regarding age, there was no significant differences between patients ≤25 years and >  25 years for all gingival parameters measurements. The relationship of smoking with different gingival parameters also showed no significant differences between smokers and non-smokers. Similarly, relationship of khat chewing with different gingival parameters showed no significant difference. Regarding inter-relationship between parameters, thin GT was associated with rectangular tooth form while square and quadrate forms are more associated with "1.5-2 mm" GT. WKG of ≤4 mm was associated with rectangular tooth form while WKG >  8 was more associated with square and quadrate forms with no significant difference. Results showed significant association between thin GT with 4.1-8 mm WKG. Conclusion Yemeni population had more prevalence of "1.5-2 mm" GT, rectangular crown shape and WKG from 4.1-8 mm. Regarding interrelationship between gingival parameters, GT showed obvious relationship with WKG, CW/CL ratio and PH. WKG with CW/CL also showed significant relationship while no relationship was shown between other gingival phenotype parameters.